PENERAPAN VALUE ENGINEERING PADA PEKERJAAN PONDASI PROYEK REHAB PASAR PAGI PROVINSI KALIMANTAN TIMUR - A. Joni Patila; Kartono Wibowo; Faiqun Ni'am (Journal of Innovation Research and Knowledge, 2025)
Pasar Pagi Samarinda, located in Gajah Mada, Samarinda, East Kalimantan, is a staple food market that is planned to be upgraded to a Type A market through a development project outlined in the Detail Engineering Design (DED). According to the DED document prepared by the consultant, the total project value is estimated to be IDR 364,459,686,000. To improve financing efficiency while maintaining construction quality, a Value Engineering (VE) analysis is required. The goal of Value Engineering is to analyze the construction design to achieve the desired function at a lower cost without compromising quality. This study aims to identify design components that can be replaced with more cost-effective alternatives while still being effective. The research method used is descriptive, both qualitative and quantitative, with analysis stages according to Value Engineering standards. The first stage involves gathering information about the initial project design. Next, a functional analysis is carried out to determine the needs of each component. During the creativity stage, alternative, more cost-efficient designs are proposed. The evaluation phase compares the alternatives based on cost and benefits, and finally, the recommendation phase provides the most cost-efficient design solution. The results show that replacing the bored pile foundation design with a pile foundation can significantly reduce construction costs. Using the pile foundation reduces the total project cost to IDR 379,536,168,000, lower than the initial design with a bored pile foundation valued at IDR 371,486,210,000. The cost savings of IDR 8,049,958,000, or about 2.12% of the total project value, indicate that the pile foundation alternative is an effective solution for reducing costs without compromising the construction quality of Pasar Pagi Samarinda